Teixobactin: a paving stone toward a new class of antibiotics? - Gunjal, Vidya B.; Thakare, Ritesh; Chopra, Sidharth; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2020)
Antimicrobial resistance is a serious threat to human health worldwide, prompting research efforts on a massive scale in search of novel antibiotics to fill an urgent need for a remedy. Teixobactin, a macrocyclic depsipeptide natural product, isolated from uncultured bacteria (Elef theria terrae), displayed potent activity against several Gram-positive pathogenic bacteria. The distinct pharmacological profile and interesting structural features of teixobactin with nonstandard amino acid (three Damino acids and L-allo-enduracididine) residues attracted several research groups to work on this target molecule in search of novel antibiotics with new mechanism. Herein, we present a comprehensive and critical perspective on immense possibilities offered by teixobactin in the domain of drug discovery. Efforts made by various research groups since its isolation are discussed, highlighting the molecule's considerable potential with special emphasis on replacement of amino acids. Critical analysis of synthetic efforts, SAR studies, and the way forward are provided hereunder.